Peranan Kegiatan Promosi Kesehatan Tentang Kehamilan Remaja Terhadap Pengetahuan Remaja di Kota Manado - Olivia Melissa Poluan; Dety Mulyanti (Jurnal Kesehatan Amanah, 2023)
Proportion of women aged 10-19 years has been pregnant 58.8 percent and 25.2 percent are pregnant in Indonesia. The purpose of writing is to determine the role of health promotion about adolescent pregnancy on adolescent knowledge in Manado. Research model by using intervention (treatment) on research subjects to determine the results of changes after being treated intervention. The instruments used were questionnaires distributed before and after health promotion (pre-post test) to see the level of knowledge of adolescents, questionnaires containing 20 questions about teenage pregnancy. The results of the study found that there was an influence of providing health promotion about pregnancy on knowledge in adolescents in Manado City.